HISTORICAL GEOGRAPHICAL CLASSIFICATION AND ECONOMIC, SOCIO-POLITICAL CLASSIFICATION OF THE GUZAR DEPARTMENT IN THE SECOND HALF OF THE XIX CENTURY CONDITION - Djalolovich, Bahrom Karimov; Xudoyqulovich, Ernazarov Azim (The journal of contemporary issues in business and government, 2021)
Principality Kelif, Zafarname, Baburname, Big Uradariya, Xuzor, Taxaristan, black horses, Akrabat, Gate of Timur, way of Kaltaminar, Aksaray, Turakurgan. 45 versts (1verst-1.06 km) to the south-east of Karshi is the city of Guzar, the center of the Guzar principality,whose geographical location is on the hills on the western slope of the Gissar mountain range. [1, -663] The principality of Guzar is bordered on the north by the upper reaches of the Great Uradarya, on the east by the Great Uradarya and the eastern part of Kirshaktog, and on the west by 35-40 latitudes. The Quyitang River, which flows through the western part of the principality, is considered to be the border of the principalities of Guzar and Kelif. The eastern, southern and western parts of the Guzar principality consist of mountainous areas found Only the north-western part of the principality, ie the part bordering on the Karshi principality, consisted of a plain. In the 19th century, the border between the principalities of Guzar and Karshibegan in the village of Yangikent, which is located at an altitude of 1,150 feet (1ft-30.48 cm) above sea level. The height of the mountains in the eastern and south-eastern part of the Guzar principality was 2200-2400 feet.² [2, -154] The cityof Guzar, the center of the Guzar principality, has been mentioned many times in many historical works about Hazrat Amir Temur, from Sharafiddin Ali Yazdi's "Zafarnoma" to Zahiriddin Muhammad Babur's "Boburnoma". [3, -7] The city of Guzar is 1530 feet, 718 mm high. [4,24] According to anothersource, the city of Guzar has an absolute height of 1310 feet and 38.36.18. north latitude and 35.53.15 east longitude. [5,34] At the end of the19th century, theclimateoftheoasiswascontinentalandarid, and them difference between the average temperature during the day and night, as well as during the winter and summer months, was very large. In winter, the snow lasts up to three months, and in some years the spring rains come.However, due to the heat of theair,evaporation was strong and the fields dried up immediately after the rain.Kashkadarya is the main river of the oasisan ditstributaries Jinnidarya, Oksuv, Yakkabogdarya, Guzardarya (along with the Big and Small Uradarya) are saturated with snow, rain and glacial water.